2015
DOI: 10.3109/02713683.2014.969808
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin Reduces Chorioretinal Damage in the Murine Laser Model of Choroidal Neovascularization

Abstract: The endogenous lactoferrin present in WT mice appears to reduce the choroidal neovascularization in the laser-induced choroidal neovascularization model in mice. Treatment with exogenous lactoferrin is capable of reducing the choroidal neovascularization in lactoferrin knockout mice but does not add a significant protective effect to WT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
(29 reference statements)
1
6
0
Order By: Relevance
“…In the current study, we found that oral administration of lactoferrin has a therapeutic effect in a laser-induced CNV model mimicking the neovascular type of AMD ( Figure 5). This result is consistent with the previous report that the CNV volume is significantly increased in lactoferrin gene knockout mice (Montezuma et al, 2015). It has been reported that HIF downstream genes were upregulated in a laser-irradiated RPE/choroid (Kurihara et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, we found that oral administration of lactoferrin has a therapeutic effect in a laser-induced CNV model mimicking the neovascular type of AMD ( Figure 5). This result is consistent with the previous report that the CNV volume is significantly increased in lactoferrin gene knockout mice (Montezuma et al, 2015). It has been reported that HIF downstream genes were upregulated in a laser-irradiated RPE/choroid (Kurihara et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, treatment of LFKO mice with exogenous LF reduced choroidal neovascularization lesions. 22 Taken together, these results establish the protective roles of LF during ocular wound healing and suggest therapeutic potentials of LF for treating ocular injuries.…”
Section: Introductionmentioning
confidence: 55%
“…Administration of additional exogenous bovine LF can further decrease the chorioretinal damage in the laser induced CNV model in mice. 22 While the mechanism of action remains unclear, it may involve LF’s role in iron binding and subsequent reduction in the Fenton Chemistry reaction that produce damaging hydroxyl radicals by laser insult. Knowing that LF is expressed in the RPE tissue is the first step in identifying the potential mechanism to explain the larger lesion volumes of LFKO versus WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…The mice’s eyes were dilated with 0.5% tropicamide and 0.5% phenylephrine eyedrops (Santen Pharmaceutical, Osaka, Japan) and anesthetized with a combination of midazolam (Sandoz, Tokyo, Japan), medetomidine (Orion, Espoo, Finland), and butorphanol tartrate (Meiji Seika Pharma, Tokyo, Japan), called MMB. The laser procedure was performed as previously reported [38]. To focus on the retina, the eyes of mice were covered with a contact lens (Haag-Streit Diagnostics, Köniz, Switzerland).…”
Section: Methodsmentioning
confidence: 99%